2019
DOI: 10.1038/s41398-019-0591-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing neuroscience-based treatments for alcohol addiction: A matter of choice?

Abstract: Excessive alcohol use is the cause of an ongoing public health crisis, and accounts for ~5% of global disease burden. A minority of people with recreational alcohol use develop alcohol addiction (hereafter equated with “alcohol dependence” or simply “alcoholism”), a condition characterized by a systematically biased choice preference for alcohol at the expense of healthy rewards, and continued use despite adverse consequences (“compulsivity”). Alcoholism is arguably the most pressing area of unmet medical need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 153 publications
1
66
0
Order By: Relevance
“…We previously reported that a history of alcohol dependence results in a persistent downregulation of Syt1 expression in the PL (8). In the present study, we examined whether this effect contributes mechanistically to behaviors characteristic of alcohol addiction (29). In support of this overall hypothesis, we found that a Syt1 KD within the PL increased alcohol selfadministration and the motivation to consume alcohol in nondependent animals, mimicking what is observed following a history of alcohol dependence.…”
Section: Discussionsupporting
confidence: 75%
“…We previously reported that a history of alcohol dependence results in a persistent downregulation of Syt1 expression in the PL (8). In the present study, we examined whether this effect contributes mechanistically to behaviors characteristic of alcohol addiction (29). In support of this overall hypothesis, we found that a Syt1 KD within the PL increased alcohol selfadministration and the motivation to consume alcohol in nondependent animals, mimicking what is observed following a history of alcohol dependence.…”
Section: Discussionsupporting
confidence: 75%
“…Specifically, rats with deficits in the expression of the γ-aminobutyric acid (GABA) transporter GAT-3 preferred alcohol over a sweet solution, and animals normally preferring the sweet solution switched their preference to alcohol following knockdown of GAT-3. Furthermore, selective reductions in GAT-3 expression in the CeA were also found in people dying with AUD ( 12 ), helping to validate the importance of this murine model.…”
Section: Introductionmentioning
confidence: 93%
“…A CCORDING to the reports published by the LANCET [1] and NATURE [2], about 5% of global burden of diseases is attributed to excessive alcohol consumption and corresponds to 6% of total deaths that occur annually. Besides, it has been established in [3], that the adverse effects of alcohol far exceed those due to illicit drugs.…”
Section: Introductionmentioning
confidence: 99%